PP.18.04: CENTRAL AND BRACHIAL BLOOD PRESSURES DIFFERENTIALLY AFFECT HYPERTENSIVE CARDIOVASCULAR ORGAN DAMAGE. (June 2015) - Takayama, S.; Takase, H.; Okado, T.; Tanaka, T.; Makino, K.; Hayashi, H.; Ohte, N.; Dohi, Y.
Abstract : Objective: Hypertension is the major risk factor for cardiovascular and cerebrovascular events and reducing brachial blood pressure in hypertensive individuals can reduce the increased risk. However, recent studies suggest that central blood pressure is more closely associated with cardiovascular events than brachial blood pressure though under controversy. The present study was designed to test the hypothesis that central and brachial blood pressures have different impact on hypertensive organ damages. Design and method: A total of 746 participants (men = 349, mean age = 61.4 years) in our physical checkup program were enrolled. Brachial blood pressure (oscillometer) and radial artery pressure waveforms (tonometer) were recorded using an automated device, and the pressure corresponding to the second systolic peak of radial pressure waveforms was taken as central blood pressure (HEM-9000AI, Omron Healthcare, Kyoto). Besides the routine checkup program, B-type natriuretic peptide (BNP), urinary albumin (expressed as the ratio of urinary albumin to creatinine concentrations [UACR]) and brachial-ankle pulse wave velocity (baPWV; BP-203RPEII, Omron Healthcare) were measured. A cross-sectional analysis was performed in order to investigate the impact of central or brachial blood pressure on target organ damages. Results: Brachial blood pressure was 128.1 ± 17.1/76.2 ± 10.6 mmHg and central blood pressure was 121.3 ± 17.8 mmHg. Both brachial blood pressure and central blood pressure were positively correlated with BNP (median = 10.7 ng/L), electrocardiogram (ECG) voltage (SV1+RV5) (mean = 2.2 mV), UACR (median = 4.2 mg/g creatinine) and baPWV (mean = 15.6 m/sec) in univariate analysis (p < 0.001). However, brachial, but not central, systolic blood pressure was significantly correlated with ECG voltage (r = 0.496, p < 0.001), UACR (r = 0.348, p = 0.012), and baPWV (r = 0.424, p < 0.001) in multivariate analysis adjusted for body mass index, heart rate, estimated glomerular filtration rate, uric acid, fasting plasma glucose, low-density lipoprotein cholesterol, hemoglobin and current smoking habit. In contrast to brachial blood pressure, central blood pressure was correlated with BNP (r = 0.311, p = 0.014) in multivariate analysis. Conclusions: Central and brachial blood pressures have different impact on cardiovascular systems. Brachial blood pressure is associated with hypertensive organ damage, whereas CAP is associated with left ventricular load. Measurement of these two indices may be more predictive for cardiovascular damages in the general population.